2018
DOI: 10.1007/s11914-018-0427-y
|View full text |Cite
|
Sign up to set email alerts
|

Good, Bad, or Ugly: the Biological Roles of Bone Marrow Fat

Abstract: Lipotoxicity in the bone is exerted by bone marrow fat through the secretion of adipokines and free fatty acids (FFA) (predominantly palmitate). High levels of FFA found in the bone marrow of aged and osteoporotic bone are associated with decreased osteoblastogenesis and bone formation, decreased hematopoiesis, and increased osteoclastogenesis. In addition, FFA such as palmitate and stearate induce apoptosis and dysfunctional autophagy in the osteoblasts, thus affecting their differentiation and function. Regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 84 publications
0
48
1
1
Order By: Relevance
“…Due to the accumulation of marrow adipose tissue [4], osteoporosis caused by obesity is characterized by an increase in marrow fat and a decrease in BMD in trabecular bone [41]. Regulating marrow adipocytes may be considered as a potential therapeutic target for osteoporosis [42]. The present study showed that knee loading reduced body weight, fat, BMI, the number, perimeter, and area ratio of adipocytes, while it elevated BMD, BMC, the circumference of trabecular bone, and the osteoblast number on the trabecular bone surface.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the accumulation of marrow adipose tissue [4], osteoporosis caused by obesity is characterized by an increase in marrow fat and a decrease in BMD in trabecular bone [41]. Regulating marrow adipocytes may be considered as a potential therapeutic target for osteoporosis [42]. The present study showed that knee loading reduced body weight, fat, BMI, the number, perimeter, and area ratio of adipocytes, while it elevated BMD, BMC, the circumference of trabecular bone, and the osteoblast number on the trabecular bone surface.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow adiposity is believed to cause high levels of fatty acids within the bone marrow milieu, which has toxic effects on osteoblasts and osteocytes [121]. A series of in vitro studies demonstrated detrimental effects of palmitic acid on bone cells [122••, 123].…”
Section: Lipids and Fatty Acidsmentioning
confidence: 99%
“…This predominant differentiation of MSCs into osteoblasts changes with age, shifting their differentiation into adipocytes. Accumulation of marrow fat plays a toxic role affecting osteoblasts as well as hematopoietic cells, exerted through the secretion of fatty acids and adipokines that accumulate in the bone marrow of aging and osteoporotic bone decreasing osteoblast differentiation, function, and survival while also stimulating osteoclastic activity (Figure ) …”
Section: Pathophysiologymentioning
confidence: 99%
“…Accumulation of marrow fat plays a toxic role affecting osteoblasts as well as hematopoietic cells, exerted through the secretion of fatty acids and adipokines that accumulate in the bone marrow of aging and osteoporotic bone decreasing osteoblast differentiation, function, and survival while also stimulating osteoclastic activity (Figure 1). 14 The pathophysiology of osteosarcopenia involves a combination of fat, muscle, and bone-related mechanisms ( Figure 2). Fat infiltration, and its associated lipotoxic effect, is observed in both muscle and bone independent of body mass index.…”
Section: Pathophysiologymentioning
confidence: 99%